Overview of Emotional Stability in Class Adolescents Based on Nursing Perspectives - Wisnusakti, Khrisna; Kumala, Tria Firza; Hidayat, Monna Maharani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Stability Emotions are not one of the determinants of a person's personality pattern, but emotional stability can help to control emotional development, one of which is adolescent development emotion teenager Step mid found experience install significant receding caused by several  factor of them environment , environment enough big the role in influence atmosphere heart Objective: The purpose of this study was to determine the emotional stability of adolescents in Al - Azhary Junior High School Cianjur , and the relationship between the two variables. Method: The method used is quantitative by design study descriptive quantitative Result: emotional stability where it was found that most of the respondents, as many as 66 (76.7%) had low emotional stability and less than half of the respondents as many as 20 (23.3%) had high emotional stability. Conclusion: Stability emotions in teenagers in at Al- Azhary Middle School Cianjur have stability low emotional , so suggested right need upgraded understanding teenager to condition mental health